PENGARUH VITAMIN E TERHADAP KADAR SGPT DAN SGOT TIKUS PUTIH GALUR WISTAR YANG DIPAPAR TIMBAL (Universitas Negeri Semarang, 2013)
This study aimed to examine the effect of the vitamin E administration on levels of SGOT and SGPT blood serum male albino rats (Rattus norvegicus) wistar strain were exposed of lead per oral. The sample used 20 male rats were divided into 4 groups:I of a control, II of the treatment of lead 175 mg/rat, III of Vitamin E 1.44 mg/rat and lead 175 mg/rat, IV of Vitamin E 2.16 mg/rat and lead 175 mg/rat for 21 days. On day 22 measured levels of SGOT and SGPT and blood lead. SGOT and SGPT data were analyzed with one-way ANOVA, followed by BNT test. The results of one-way ANOVA showed antioxidant vitamin E giving a significant effect on the levels of SGOT and SGPT (p <0.05) rats. The BNT test SGOT levels showed a significant difference except in group II and III, the SGPT levels showed a significant difference except in group III and IV. From the results of this study concluded that the affects of vitamin E decrase levels of SGOT and SGPT blood serum of male albino rats (Rattus norvegicus) wistar strain were exposed to lead per oral.